Precarious Voices? Types of “Political Citizens” and Repertoires of Action among European Youth - Lara Monticelli (Coordinamento SIBA, 2017)
This article’s goal is to explore the existence of ‘political citizens’ profiles across three European cities (Turin, Cologne and Lyon) and to ascertain the role of an unstable occupational status on the repertoires of action deployed. For this purpose, a technique called latent class cluster analysis (LCCA) is applied to a large sample, including young precarious and regular workers (deployed as a reference group). This technique allowed us to derive five descriptive probabilistic profiles of ‘political citizens’ and their repertoires of action in each city. The empirical findings underline the emergence of hybrid repertoires of action together with ‘single-issue’ or ‘cause-oriented’ forms of political participation. This study represents an attempt to encourage the dialogue between two strands of research in social sciences, namely sociology of work and political participation and to foster the formation of an innovative research agenda crossing these two fields.